2016
DOI: 10.1088/1748-9326/11/9/094008
|View full text |Cite
|
Sign up to set email alerts
|

Mapping water consumption for energy production around the Pacific Rim

Abstract: World energy demand is projected to increase by more than a third by 2035 and with it the use of water to extract and process fuels and generate electricity. Management of this energy-water nexus requires a clear understanding of the inter-related demands of these resources as well as their regional distribution. Toward this need the fresh water consumed for energy production was mapped for almost 12 000 watersheds distributed across the 21-economies comprising the Asia-Pacific Economic Cooperation. Fresh wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…A final general finding is that most (80%-95%) water consumption for electricity is fresh ( figure 5). Consistent with previous findings [35], this reliance on freshwater suggests that the electricity sector competes with other freshwater users (e.g. agriculture, ecosystems, and municipalities) for water access.…”
Section: Resultssupporting
confidence: 89%
“…A final general finding is that most (80%-95%) water consumption for electricity is fresh ( figure 5). Consistent with previous findings [35], this reliance on freshwater suggests that the electricity sector competes with other freshwater users (e.g. agriculture, ecosystems, and municipalities) for water access.…”
Section: Resultssupporting
confidence: 89%
“…Figure 9 shows the total energy related water consumption mapped over regional water risk in China. Ten sectors are involved in the analysis of water consumption on energy production, including the biofuel feedstock production, energy processing including biofuels and oil, energy production including oil, gas, coal, uranium, and unconventional oil and gas, hydroelectric and thermoelectric power (Tidwell and Moreland 2016). The watershed and energyrelated water consumption locations have high energywater risk.…”
Section: Analysis Of Potential Water Resources Risks In Energy Production Of Chinamentioning
confidence: 99%
“…There are in total 1630 watersheds in China, 764 of which have water risks. Regarding the energy-related water consumption, there are 440 watersheds and 54% of them have energy-water risks (Tidwell and Moreland 2016). Generally, it can be concluded that China has a high risk of water consumption related with energy production.…”
Section: Analysis Of Potential Water Resources Risks In Energy Production Of Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have published a series of spatially-explicit studies to determine where energy production is needed to meet water demand in the western United States and globally [13][14][15]. These studies relied on top-down aggregated estimates of water use from the US Geological Survey and do not calculate energy embedded in water consumed in a particular location.…”
Section: Contributors To Electricity MIXmentioning
confidence: 99%